Zagreb Polynomials and Redefined Zagreb Indices for Chemical Structures Helpful in the Treatment of COVID-19 - Abaid ur Rehman Virk (Scientific Inquiry and Review, 2020)
A topological index (TI) is a number that is helpful in predicting the properties of chemical compounds. We can estimate the physical and chemical properties of several chemical compounds. In this study, we compute Zagreb polynomials and the redefined Zagreb indices for chemical compounds used in the treatment of COVID-19 namely remdesivir, chloroquine, hydroxychloroquine and theaflavin.Copyright(c) The Author